2014
DOI: 10.1626/pps.17.237
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Uptake by the Rice Plant and Changes in the Soil Chemical Properties in the Paddy Rice Field during Yearly Application of Anaerobically-Digested Manure for Seven Years

Abstract: This study investigated the changes in the chemical properties of the plow soil during a 7-year period with yearly application of anaerobically-digested manure (ADM), and the effect of the different ADM application methods on nitrogen (N) uptake by rice plants and the apparent N balance (input N minus output N). Among the treatments significant differences were observed in the pH, total N, and available N in the plow soil. The cumulative N uptake by rice plants in the ADM split application plots was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Different lowercase alphabets indicate significant differences (P < 0.05). (Nishikawa et al 2014) and could reduce grain quality. Indeed, we provide partial evidence that the application of residual slurry can balance improvements in grain yield while controlling methane emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Different lowercase alphabets indicate significant differences (P < 0.05). (Nishikawa et al 2014) and could reduce grain quality. Indeed, we provide partial evidence that the application of residual slurry can balance improvements in grain yield while controlling methane emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown that organic amendments play a crucial role in both short-term nutrient supply and long-term build-up of soil quality in flood-irrigated rice crops (Javier et al, 2002;Knoblauch et al 2012;Nishikawa et al, 2014). In addition, when properly managed, they decrease potential polluters and increase yield, which makes them important sources of income and added value, since they are resources available on the farms and may be used in organic production (Liang et al, 2017;Mushtaq et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In flood-irrigated rice, organic fertilizers must be incorporated into dry soil approximately 30 days before soil flooding and rice sowing, to enable the mineralization process and to prevent the formation of organic acids during the anaerobic decomposition of organic material (Reunião…, 2016). Applying poultry manure to rice plants at their developmental stages has negative practical implications and causes environmental pollution (Nishikawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given that fertilizer was applied in the rice-cultivated fields during the prior planting season and that the fallow fields were not fertilized and irrigated for at least 5-10 years, the comparable levels of total N, P and K across both fallow and cultivated soils at the postharvest time of sampling suggests loss of nutrients in the rice-cultivated soils. Such loss of nutrients may be due to biochemical processes, such as denitrification, ammonia volatilization and clay fixation, as well as nutrient losses in water runoff, deep percolation and uptake by the rice cultivars [90][91][92]. Moreover, the observed significant reduction in ammonium (NH 4 + -N), nitrate (NH 4 + -N), and K between postharvest (PH) and pre-planting (5mR) in both Umbeluzi and Chokwe also suggest further leaching, nutrient adsorption (e.g., insoluble phosphates due to binding on clay particles, Al and Fe hydroxides/oxides) and/or oxidation of nutrients during the off-season.…”
Section: Discussionmentioning
confidence: 99%